Эпидемиология лимфогранулематоза в Украине в 1991–1998 гг. - Кривец, Д.Я. (Онкологія, 2001)
Рассчитаны показатели заболеваемости лимфогранулематозом (С81) населения областей Украины, АР Крым и г. Киева. Проанализированы возрастно-половые особенности и оценены динамические тенденции заболеваемости населения изучаемых территорий. Выявлена тенденция к росту заболеваемости лимфогранулематозом мужского и женского населения г. Киева в возрасте 20–24 лет в 1991–1998 гг. Установлены различия в уровне заболеваемости в отдельных экономико-географических зонах Украины. Based on the data about the cases of Hodgkin’s disease (C81) revealed, the morbidity parameters are estimated for the regiones of Ukraine, the Autonomic Republic Crimea and Kyiv. The age- and sex-related features are analyzed and the dynamic morbidity tendencies in the population of the territories studied are assessed. The tendency is revealed showing that the incidence of Hodgkin’s disease grew in both male and female populations of Kyiv aged 20–24 years between 1991–1998. The distinction in the morbidity levels are shown between certain economic/ geographical zones of Ukraine.